Defatted kenaf seed meal (DKSM) : prospective edible flour from agricultural waste with high nutritive values and antioxidant activity. - Kim, Wei Chan; Khong, Nicholas Mun Hoe; Iqbal, Shahiq; Ismail, Maznah
Kenaf seeds are primary by-product of kenaf plantation. Recently, kenaf seed oil has been proposed as a new source of functional edible oil with promising antioxidant activity and anticancer properties. As kenaf seed only contains approximately 20% oil, massive extraction of kenaf seed oil will eventual1y result in the production defatted kenaf seed meal (DKSM) in considerably large quantity. DKSM is potentially used as an alternative and new emerging source of functional food ingredient. Our studies show that DKSM is high in protein (26.19%) and carbohydrate (57.09%), accompanied with magnesium, potassium and phosphorus as the major dietary minerals (> 1%) within. On the aspect of nutraceutical values, DKSM exhibited appreciably higher total phenolic content (3399.37 ug GAE/g defatted material), total flavonoid content (251.00 ug RE/g defatted material) and antioxidant activity as compared to several tested commercial edible flours (wheat, rice and sweet potato). Gal1ic acid, (+)-catechin, 4-hydroxybenzoic acid, vanillic acid and syringic acid were found to be the predominant phenolics in DKSM. Acute toxicity study indicated that DKSM is safe for oral consumption and did not demonstrate any adverse toxic reactions to the rats at the dosage as high as 2000 mg/kg body weight. On the basis of our studies, DKSM is prospectively commercialized as a safe, highly antioxidative and nutritive edible flour/ingredient for value-added nutraceutical and functional food products.